GAMBARAN RESPON IBU PADA ANAK DENGAN DEMAM PASCA IMUNISASI DIFTERI PERTUSIS TETANUS (DPT) - Wahyunengsih, Sry "; ", Erwin "; Amir, Yufitriana " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2017)
AbstractThis study aims to reveal the mother's response in the face of fever in children post-immunization Difteri, Pertusis, Tetanus (DPT). This research uses descriptive design simple. This research was conducted in public health Sungai Sembilan of the 84 samples taken using purposive sampling technique by observing the inclusion criteria. Measuring instrument used in this study is a questionnaire. The analysis is univariate analysis were performed to analyze the frequency distribution of each variable. The results showed that perceptions of fever is a normal reaction to a DPT immunization by 77 (91.7%), fever relief efforts for the handling of 39 (46.4%), and the actions taken to address maternal fever in children as many of 36 (42, 9%). The results of this study can be a reference for the mother in order to improve the mother's response when a child has a fever after immunization of DPT Keywords: Response mother, fever, DPT immunization.Bibliography: 27 (2003-2016)